EXTH-97. BONE MARROW-DERIVED ENGINEERED MYELOID CELLS ENHANCE THE TRAFFICKING AND ACTIVATION OF CYTOTOXIC T CELLS IN THE GLIOMA MICROENVIRONMENT. (14th November 2022) - Canella, Alessandro; Nazzaro, Matthew; Schmitt, Claire; Rajendran, Sakthi; Haffey, Abigail; Nigita, Giovanni; Thomas, Diana; Rajappa, Prajwal
Abstract: INTRODUCTION: Gliomas are the most prevalent type of brain tumors in the adolescent and young adult population (AYA) and one of the leading causes of cancer- related death. Two-third of glioma AYA patients are affected by low-grade gliomas (LGGs), but yet there are no specific treatments. Therefore, a significant percentage of LGG patients experience tumor recurrence and malignant progression to high-grade glioma (HGG) and the immune microenvironment plays a critical role in mediating mechanisms of tumor progression and treatment resistance. Specifically, tumor associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) have been shown to restrict cytotoxic effector trafficking and activation. To that end, first-line immunotherapies have limited efficacy in improving outcomes for HGGs. HYPOTHESIS: We investigated the preclinical efficacy of a novel immunotherapeutic approach for the treatment of LGGs in AYA mice to modulate and reprogram the immunosuppressive tumor microenvironment (TME) and enhance the trafficking of activated effector T cells. METHODS: Immunocompetent RCAS n/tv-a LGG bearing animals were treated at day 28 with a single retroorbital dose of bone-marrow derived myeloid cells, engineered for the release of Interlekin-2 (GEMys-IL2). The treatment was well tolerated and no sign of toxicity was noted. RESULTS: Our results demonstrated that GEMys-IL2 efficiently crossed the BBB, infiltrate the glioma microenvironment, and activate infiltrating immune cells while altering the TME underscored by an increased CD8+ T cell population. Of note, the RCAS/t-va immunocompetent LGG to HGG progression mouse model treated with a single dose of GEMys-IL2 demonstrated a transient arrest of tumor burden within 14 days post treatment, which was associated with a significant advantage in overall survival. CONCLUSIONS: These results highlight the pre-clinical efficacy and anti-tumoral therapeutic activity of GEMYys-IL2 on CD8+ T cell trafficking and activation to the TME in low-grade glioma in vivo, thus supporting its potential as a novel cell-mediated innate immunotherapy.